2013
DOI: 10.1007/s10706-013-9648-0
|View full text |Cite
|
Sign up to set email alerts
|

The Low Compaction Grading Technique on Steep Reclaimed Slopes: Soil Characterization and Static Slope Stability

Abstract: Since the Surface Mining and Control Reclamation Act of 1977, US coal mining companies have been required by law to restore the approximate ground contours that existed prior to mining. To ensure mass stability and limit erosion, the reclaimed materials have traditionally been placed with significant compaction energy. The Forest Reclamation Approach (FRA) is a relatively new approach that has been successfully used to facilitate the fast establishment of native healthy forests. The FRA method specifies the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Plants growing in uncompacted LGM in a real environment, i.e., abandoned quarries, should not have this good performance because the only water source was LGM, which contained only 5 % water under natural precipitation. R. pseudoacacia growing in CL3 should have the best performance in the real environment although the germination, survival and growth were not significantly different from CL1 in our experiment, which was consistent with Jeldes et al (2013).…”
Section: Using Compacted Lgm As Growth Substrate For Plantssupporting
confidence: 85%
“…Plants growing in uncompacted LGM in a real environment, i.e., abandoned quarries, should not have this good performance because the only water source was LGM, which contained only 5 % water under natural precipitation. R. pseudoacacia growing in CL3 should have the best performance in the real environment although the germination, survival and growth were not significantly different from CL1 in our experiment, which was consistent with Jeldes et al (2013).…”
Section: Using Compacted Lgm As Growth Substrate For Plantssupporting
confidence: 85%
“…The study sites were devoid of native soils and forest cover, covered by surface mining spoils 1.5–2.0 m deep composed of silty‐clay soils mixed with gray shale and brown sandstone rocks. Classified by the Unified Soil Classification System (USCS), spoil materials were gravel with significant clay fines (GC) (Jeldes et al ., ). Average % rock by weight, defined as coarser than 25.4 mm (gravel size), were estimated at each study site as: Premium: 24.8%, National: 24.6%, Mountainside: 11%.…”
Section: Methodsmentioning
confidence: 74%
“…In the journal articles, the use of active voice and human subjects was rare. Within literature reviews, author names were occasionally used as agents in sentences—for example, “Sweigard et al (2007a) have suggested correlations between…” (Jeldes, Drumm, & Schwartz, 2013, p. 1262)—but even those occurrences were relatively uncommon. Observations and recommendations were usually stated in passive voice, as in Sample 4: 4.…”
Section: Resultsmentioning
confidence: 99%
“…. " (Jeldes, Drumm, & Schwartz, 2013, p. 1262)-but even those occurrences were relatively uncommon. Observations and recommendations were usually stated in passive voice, as in Sample 4:…”
Section: Differences Between Practitioner Reports and Journal Articlesmentioning
confidence: 99%